ANALISIS RENDERING PERFORMA ANTARA SERVER SIDE DAN CLIENT SIDE PADA WEB APPLICATION - Herman; Alvi Geovanny (P3M Institut Teknologi Pagar Alam, 2022)
One way to access information is to use a website. A web application is an application that can be accessed from a web browser via the Internet or an intranet network. This development resulted in a lot of user traffic affecting website performance, so that the term client-side rendering emerged, although currently server-side rendering is still proven to be faster, but the popularity of frameworks that use client-side actually ranks first. Therefore, the purpose of this research is to design two websites where both frameworks use the Javascript programming language, named ReactJS for the client-side and NextJS for the server-side.